When World and Worldview Clash: Orthodoxy, Ecology, and the Issue of Phthora - Gschwandtner, Christina M. (Zygon, 2025)
The ancient Greek notion of phthora (perishing, ceasing to be, disintegration, corruption, defilement) is absolutely crucial for Orthodox theology and deeply inscribed in its liturgy. Yet, it no longer represents how we generally think about the cosmos and the material world. This article examines the role of this notion in the Orthodox patristic worldview and its contemporary relevance. It first explains the philosophical background to the notion before going on to show how it is appropriated by patristic thinkers for major theological doctrines and deeply shapes the worldview communicated by liturgical practice. It concludes by highlighting the complexity of the issue and pointing to the kinds of challenges contemporary Orthodox theologians would have to address if they wanted to employ this notion for making a substantive theological contribution to contemporary debates.